Night in Shanghai [compact disc, unabridged] - Mones, Nicole (Tantor Media, Inc., 2014)
In 1936, classical pianist Thomas Greene is recruited to Shanghai to lead a jazz orchestra of fellow African-American expats. Song Yuhua is refined and educated, and has been bonded since age eighteen to Shanghai's most powerful crime boss. Only when Shanghai is shattered by the Japanese invasion do Song and Thomas find their way to each other. Torn between music and survival, they are borne on an irresistible riff of melody and improvisation.